Ecosystem Services in the Dravinja Valley Bioregion - Vovk, Ana (Journal for Geography, 2024)
The Dravinja Valley bioregion is an area along the Dravinja River. It covers the valley bottom as wells as the outskirts and the upper part of the Dravinjske Gorice Hills. In this research, we were interested in the assessment of the ecosystem services based on the ecosystems represented here, which are determined according to the natural landscape properties. We evaluated four groups of ecosystems with the help of a diagram of the value of ecosystem services, which are based on the intensity of use of space. The higher it is, the lower the ecosystem services. We have taken into account the well-established division of ecosystem services into supporting, provisioning, regulating and cultural services. The research supports the interest of the municipality of Poljčane to establish the Dravinja Valley Bioregion. The assessment results of the ecosystem services show that regardless of other characteristics of the area, forest and primary vegetation play a key role in supporting environmental services.